Web GIS Decision Support System for Increasing Community Participation in Urban Spatial Planning Using Hybrid AHP-TOPSIS - Agus, Fahrul; Azhari, Muhamad; ., Kusnandar (International Journal of Engineering and Technology, 2018)
The implementation of the GIS Decision Support System in spatial land management is believed to increase community participation to contribute to solving land management problems. The objective of the study was to analyze weighting parameters and prioritize the loca-tion of urban forest as Green Open Space (GOS) in Balikpapan City-Indonesia. Weighting and priority ranking analysis uses a combi-nation of 2 methods on Multicriteria Decision Analysis - MCDA i.e. hybrid AHP-TOPSIS. The research phases were conducted by in-depth survey method to explore the preference of respondent key-person to the comparison value of each parameter. There has been a description of the existence of urban GOS, parameter weighting value and priority order of urban forest as an alternative location of Balikpapan City GOS. Weight analysis yields land area as the main factor in determining GOS location, followed by land price and location distance to downtown. The forest city location of Bendali III Gunung Bahagia Village in South Balikpapan is the highest priori-ty that can be used as development area GOS Balikpapan City. Web GIS prototype software has been created as a decision support system that can give priority recommendations for urban forest as GOS Balikpapan City.
Keywords: Urban Green Open Space; Weighting Analysis; MCDA; AHP-TOPSIS; Balikpapan City